OPTIMAL PREPARATION OF ROSA CENTIFOLIA ‘UAF’ CUTTINGS - I. Ahmad; K. Ziaf; M. Shahid; H. A. Iqbal; H. A. Saeed; H. K. Ali (Journal of Animal and Plant Sciences, 2021)
Rosa centifolia ‘UAF’ is being commercialized as a rose with high potential market value. A study was conducted comparing plantings from Nov. 24th to Feb. 10th in a subtropical climate. Traditional callusing method (cuttings buried in moist soil for 15 d) was compared to the use of synthetic auxins. Three experiments were set up in a split plot design having four replicates of 200 cuttings each. Cuttings planted on 24th Nov. and treated with indole 3-butyric acid (IBA) exhibited best survival rate (83%), highest number of leaves per branch (20) and number of branches per cutting (4). Among cutting types, hardwood cuttings treated with naphthalene acetic acid (NAA) had highest number of leaves per branch (6.5), plant diameter (13.3 cm) and fresh (3.0 g) and dry weight of a shoot (1.3 g). While cuttings prepared with straight cut on upper end and a slanting cut on lower end and treated with (NAA) application had better sprouting percentage (68.0%), number of branches per plant (2.9) and root length (17.7 cm). In summary, hardwood cuttings, with straight upper and slanting cut on lower end, prepared during early propagation season (Nov. 24th) and dipped in IBA solution for 5-10 sec. proved best for enhancing rooting percentage and survival rate of Rosa centifolia ‘UAF’ cuttings and may be used by nurserymen for commercial propagation.
Keywords: Propagation; rose; synthetic auxins; callusing; nursery raising